ЕҢБЕКТІ ЫНТАЛАНДЫРУ МЕН МОТИВАЦИЯЛАУ ЖҮЙЕСІН ҚҰРУ КӘСІПОРДАРДЫҢ ӘЛЕУМЕТТІК САЛАСЫН БАСҚАРУ ФАКТОРЫ РЕТІНДЕ - Z. K. Chulanova; F. N. Estybay (Экономика: стратегия и практика, 2018)
The article explores the issues of material and moral stimulation of labor based on the use of modern forms of motivation of personnel from both state and private enterprises. Various management methods aimed at increasing the employees’ interest in production results are considered. Offers are given on the use of social, organizational, economic mechanisms that help to solve social issues of the enterprise, create a favorable climate, increase the responsibility of employees for increasing the potential of the enterprise.